CHOP deletion and anti-neuroinflammation treatment with hesperidin synergistically attenuate NMDA retinal injury in mice. (December 2021) - Sato, Kota; Sato, Taimu; Ohno-Oishi, Michiko; Ozawa, Mikako; Maekawa, Shigeto; Shiga, Yukihiro; Yabana, Takeshi; Yasuda, Masayuki; Himori, Noriko; Omodaka, Kazuko; Fujita, Kosuke; Nishiguchi, Koji M.; et al.
Abstract: Glaucoma is a leading cause of blindness worldwide and is characterized by degeneration associated with the death of retinal ganglion cells (RGCs). It is believed that glaucoma is a group of heterogeneous diseases with multifactorial pathomechanisms. Here, we investigate whether anti-inflammation treatment with an ER stress blockade can selectively promote neuroprotection against NMDA injury in the RGCs. Retinal excitotoxicity was induced with an intravitreal NMDA injection. Microglial activation and neuroinflammation were evaluated with Iba1 immunostaining and cytokine gene expression. A stable HT22 cell line transfected with an NF-kB reporter was used to assess NF-kB activity after hesperidin treatment. CHOP-deficient mice were used as a model of ER stress blockade. Retinal cell death was evaluated with a TUNEL assay. As results, in the NMDA injury group, Iba1-positive microglia increased 6 h after NMDA injection. Also at 6 h, pro-inflammatory cytokines and chemokine increased, including TNFα, IL-1b, IL-6 and MCP-1. In addition, the MCP-1 promoter-driven EGFP signal, which we previously identified as a stress signal in injured RGCs, also increased; hesperidin treatment suppressed this inflammatory response and reduced stressed RGCs. In CHOP-deficient mice that received an NMDA injection, the gene expression of pro-inflammatory cytokines, chemokines, markers of active microglia, and inflammatory regulators was greater than in WT mice. In WT mice, hesperidin treatment partially prevented retinal cell death after NMDA injury; this neuroprotective effect was enhanced in CHOP-deficient mice. These findings demonstrate that ER stress blockade is not enough by itself to prevent RGC loss due to neuroinflammation in the retina, but it has a synergistic neuroprotective effect after NMDA injury when combined with an anti-inflammatory treatment based on hesperidin. Highlights: Hesperidin, a plant-derived flavonoid, attenuated microglial activation and neuroinflammation in NMDA-injured retina. NMDA-induced neuroinflammation was promoted in CHOP-deficient mice. Combination with ER stress blockade and anti-neuroinflammation had synergistically effect for retinal neuroprotection.